Particle reactors for solar thermochemical processes. (1st November 2017) - Kodama, Tatsuya; Bellan, Selvan; Gokon, Nobuyuki; Cho, Hyun Seok
Highlights: Recent developments of solar particle reactors for solar thermochemical processes have been reviewed. Presents review of particle reactors for solar two-step water splitting with metal oxides. Presents review of direct and indirect particle reactors for metal oxide processes. Presents review of solar gasification using particle reactors. Abstract: Utilization of solar thermal power for high temperature fuel production has the potential to significantly reduce the fossil fuel dependence of our current economy. Over the past two decades, remarkable progress has been made in the development of solar driven thermochemical reactors for the production of hydrogen and syngas as they are promising energy carriers for transportation, domestic and industrial applications. However, there are solar peculiarities in comparison to conventional thermochemical processes – high thermal flux density and frequent thermal transients because of the fluctuating insolation-, and conventional industrial thermochemical reactors are generally not suitable for solar driven reactors. Therefore, solar-specific modifications of reactor design are necessary to realize efficient solar driven thermochemical processes. In solar thermochemical reactors, the methods for solar-heating particulate solid feedstock to high temperatures can be broadly classified as solar "directly" and "indirectly" absorbing reactors. On solar thermochemical processes involving reacting solid particles at high temperatures, such as "solar two-step water splitting with metal oxides" and "solar gasification", various types of solar directly and indirectly absorbing particle reactors have been developed. In this review, recent development of solar particle reactors for the above solar thermochemical processes is described.